Comprehensive oral rehabilitation of a hearing-impaired patient - König János; Tamás Déri; Péter Hermann (Hungarian Dental Association, 2023)
According to some estimates, there are 60 000 hearing impaired people in Hungary. Their dental care can be difficult depending on the extent and type of hearing loss. It is the dentist's job to ensure that communication is not impaired by speaking directly and clearly, ensuring that the mouth can be read and sometimes signalling through an interpreter or written communication. The patient has the right to obtain informed consent to dental treatment. We try to give an insight into the difficulties of care by presenting the complete oral rehabilitation of a hearing-impaired patient.